PERANAN TES KUIS DALAM MENINGKATKAN MOTIVASI PEMBELAJAR DALAM MEMAHAMI TATA BAHASA JEPANG TINGKAT DASAR - Sastranegara, Jeni Putra (Universitas Pendidikan Indonesia, 2017)
Motivation to learn is very complicated to be examined because it involves various aspects, including the psychology of learners. However, efforts to improve the motivation of learners is not impossible for every teacher. As one of these efforts, the researcher undertook a comparative study by examining the achievement of bunpou understanding in the class that used the quiz tests and did not use the quiz test. After that, we compared with the average of semester final exam grade of the two classes. The quiz tests were formatively conducted after mid term exam until semester final exam. The result of a class that uses a quiz test has a higher average grade than a class that does not use. The mid term exam is difficult than final exam, it causes the average of the grade of student went down. However, the class that does not use the quiz test has drop two fold than the class that used the quiz test. It can be assumed that the quiz test is one of the media that has a role to increase the extrinsic motivation of the basic learner in understanding bunpou.Keywords: learning motivation, quiz tests, roles, bunpou